Peningkatan Motivasibelajar Membaca Al-Quran Menggunakan Penerapan Model Problem Based Learning di KLS IV UPTD SDN 02 Labuah Gunuang - Nurlela Nurlela; Emi Aftapik; Alhusni Fuad; Desri Wahyuni; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research was motivated by the low ability of children to read the Al-Quran in class IV at UPTD SD N 02 Labuah Gunuang. One solution to this problem is to implement activities using the PBL method. This research aims to improve the Al-Quran reading ability of children in Class IV UPTD SD N 02 Labuah Gunuang. The method used in this research is the Classroom Action Research (PTK) method. This classroom action research was carried out in 2 cycles, in each cycle there were 2 meetings. Data collection techniques used were observation and documentation. The results of this study show an increase in children's scores from pre-action, cycle I and cycle II which can clearly be described as follows: the BB score at pre-action was 11 children or 55%, then in cycle 1 it became 5 children or 30%, then in cycle II it became 0 children or 0% MB value in pre-action 2 children or 10%, then in cycle 1 it becomes 2 children or 10% In cycle II it becomes 0 children or 0%, BSH value in the action there are 2 children or 10%, then in cycle 1 became 2 children or 10%, for cycle II 2 children 10%, the BSB value in pre-action was 5 children or 25% then in cycle 1 it became 5 children or 25% and in the end cycle II increased to 17 children or 85%. Based on the results of the research above, the researcher suggests to teachers to make activities using the PBL method an alternative activity in improving children's ability to read the Al-Quran.